Using lessons learnt from key stakeholders to increase support for scaling the Reach Up Early Childhood Parenting program - Coore-Hall, Jacqueline; Smith, Joanne; Kelly, Melissa; Baker-Henningham, Helen; Chang, Susan; Walker, Susan (Frontiers in Public Health, 2023)
Introduction Sustainable implementation of early childhood programs requires resources, materials and methods that are adaptable, scalable and feasible for delivery through multiple sectors. Additional or modified program resources may be required to meet emerging needs, as programs go to scale. An active and effective monitoring, evaluation and learning (MEL) process may enable programs to be responsive to demands. The Reach Up: Early Childhood Parenting program, is designed primarily for disadvantaged children under 4 years of age in low- and middle-income countries (LMICs) to promote their development through playful caregiver interactions. The curriculum, training manuals and other materials and resources support implementers in the adaptation of the intervention, implementation, workforce training, monitoring and evaluation. This paper reports on how data collected from key informants drove modifications to program processes, materials and resources. Methods We conducted in-depth interviews with 14 key informants (including program managers, lead trainers, academics, consultants and workforce personnel) on their experiences with Reach Up across 15 LMICs where the program has been implemented. We also reviewed written records generated from (i) structured small group discussions at a Knowledge Exchange meeting of 31 Reach Up partners and (ii) notes from working groups formed at the meeting and tasked to continue working post-meeting to find solutions to support ongoing implementation. The transcripts from the in-depth interviews and the meeting records were analysed using thematic analysis with a mixture of pre-defined categories and data-driven sub-themes. Results The main findings indicated that there was a need to: (i) develop advocacy and communication resources and materials to aid prospective implementers and other stakeholders, to make decisions for implementation, (ii) revise and/or add to the content and format of the curriculum and add content in the training and other supporting manuals and (iii) enhance the training process. Conclusion: The feedback from the key global partners informed the development of new knowledge materials, resources and processes and modifications to existing program materials and resources. These will help to support advocacy, ongoing implementations, and the process of transitioning the Reach Up early childhood intervention to scale.